The own-group bias in face processing: the effect of training on recognition performance - Wittwer, Tania (Department of Psychology, 2021)
The own-group bias in face recognition (OGB) is the greater facility to distinguish and recognize people from one's own group at the expense of people from other-groups. The OGB has been studied for many years, however, very little research focuses on finding a way to decrease or eliminate it, through training. Reporting five studies involving memory or matching tasks, the aim of the present thesis was to develop and to explore to what extent training can decrease or remove the OGB. French White participants, and South African White, Black and Coloured participants took part in different studies, using Black and White faces as stimuli. In each study, White participants from both countries presented the expected OGB prior to any intervention. However, the presence of the OGB in South African Black participants was detected only in one (matching task) study, instead recording a higher discrimination performance by Black participants for White faces in the other studies. As expected, South African Coloured participants did not display increased discrimination performance for any of the other stimuli groups, both being out-group stimuli. Results from the training studies revealed either (a) no effect of a distributed training in feature focus over 5 weeks; (b) an increase of the OGB after a focus on critical facial features; (c) a decrease of the OGB in a task-specific training using pictures whose quality had been manipulated, and; (d) an important implication of the presence/absence of the target in a field detection study. With some promising results, the present work contributes to our understanding of how training could be used to improve face-recognition, and especially other-group face recognition.